Anhydrous reverse micelle nanoparticles: new strategy to overcome sedimentation instability of peptide-containing pressurized metered-dose inhalers. (1st January 2017) - Huang, Zhengwei; Wu, Han; Yang, Beibei; Chen, Longkai; Huang, Ying; Quan, Guilan; Zhu, Chune; Li, Xing; Pan, Xin; Wu, Chuanbin
Abstract: The objective of this study was to develop a novel anhydrous reverse micelle nanoparticles (ARM-NPs) system to overcome the sedimentation instability of peptide-containing pressurized metered-dose inhalers (pMDIs). A bottom-up method was utilized to fabricate ARM-NPs. Tertiary butyl alcohol (TBA)/water system, freeze-drying and lipid inversion method were successively used to produce the ARM-NPs for pMDI. Various characteristics of ARM-NPs were investigated including particle size, morphology, secondary structure of the peptide drug, aerosolization properties and storage stability. As revealed by the results, ARM-NPs with spherical shape possessed 147.7 ± 2.0 nm of particle size with 0.152 ± 0.021 PdI. The ARM-NPs for pMDI had satisfactory fine particle fraction (FPF) value of 46.99 ± 1.33%, while the secondary structure of the peptide drug was unchanged. Stability tests showed no pronounced sedimentation instability for over 12 weeks at 4–6 °C. Furthermore, a hypothesis was raised to explain the formation mechanism of ARM-NPs, which was verified by the differential scanning calorimetry analysis. The lecithin employed in the reverse micelle vesicles could serve as a steric barrier between peptide drugs and bulk propellant, which prevented the instability of peptide drugs in hydrophobic environment. Homogenous particle size could avoid Ostwald ripening phenomenon of particles in pMDIs. It was concluded that the ARM-NPs for pMDI could successfully overcome sedimentation instability by the steric barrier effect and homogeneous particle size.